Radical cystectomy: Analysis of trends in UK practice 2004–2012, from the British Association of Urological Surgeons' (BAUS) Section of Oncology Dataset. (January 2016) - Cresswell, J; Mariappan, P; Thomas, SA; Khan, MS; Johnson, MI; Fowler, S; ,
Objective: To analyse the British Association of Urological Surgeons' (BAUS) radical cystectomy (RC) dataset, to examine the trends in patient selection, use of neoadjuvant chemotherapy (NAC) and operative technique. Methods: Data for RC were entered into a database voluntarily, by operating surgeons. A comparison was made to the Hospital Episode Statistics (HES) data, to estimate the proportion of cases captured by the dataset. Results: From 2004 to 2012, data was collected on 5321 patients undergoing RC. This constituted 37.1% of all HES RC cases during the corresponding time period. Notable trends were: An increasing use of NAC, the introduction of minimally-invasive surgery (23.5% in 2012), a dramatic reduction in blood transfusion rates and the increasing yields from lymph node dissection. The ileal conduit urinary diversion predominated as the urinary diversion of choice (80% of cases). Conclusions: This analysis of a large multi-centre dataset provides insight into RC practice in the UK, over 8 years. The major weaknesses of the study were that only one-third of cases were recorded and that outcome data was very limited. Mandatory publication of outcome data from 2016 should increase the recording of cases and provide material for a more complete analysis.